2001
DOI: 10.1103/physrevb.65.014303
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the phonon entropy of vanadium

Abstract: The phonon density-of-states ͑DOS͒ of elemental vanadium was measured at elevated temperatures by inelastic neutron scattering. The phonon softening predicted by thermal expansion against the bulk modulus is much larger than the measured shifts in phonon energies. We conclude that the phonon anharmonicities associated with thermal expansion are largely canceled by effects from phonon-phonon scattering. Prior measurements of the heat capacity and calculations of the electronic entropy of vanadium are assessed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 18 publications
5
32
3
Order By: Relevance
“…The measurements on pure V with the Pharos and LRMECS time-offlight neutron spectrometers are in very good agreement at all temperatures, and also with the three-axis data reported previously. 16 The anomalous lack of softening of the phonons in pure V is clearly seen in all measurements. The phonon DOS of V is essentially constant from 10 K to 1273 K, subject only to broadening.…”
Section: Phonon Density Of Statesmentioning
confidence: 70%
See 1 more Smart Citation
“…The measurements on pure V with the Pharos and LRMECS time-offlight neutron spectrometers are in very good agreement at all temperatures, and also with the three-axis data reported previously. 16 The anomalous lack of softening of the phonons in pure V is clearly seen in all measurements. The phonon DOS of V is essentially constant from 10 K to 1273 K, subject only to broadening.…”
Section: Phonon Density Of Statesmentioning
confidence: 70%
“…The phonon DOS of V is essentially constant from 10 K to 1273 K, subject only to broadening. In the three-axis measure-ments, it was found that this behavior changes at higher temperatures, and the phonon DOS of V softens between 1273 K and 1673 K. 16 The anomalous behavior from 10 K to 1273 K is particularly strong for the high-energy longitudinal modes between 26 meV and 31 meV, whose energy clearly increases with temperature. On the other hand, the low-energy transverse phonons soften between 10 K and 1273 K, but this softening is smaller than expected from thermal expansion over such a wide temperature range ͑see discussion below on expected quasiharmonic behavior͒.…”
Section: Phonon Density Of Statesmentioning
confidence: 99%
“…We expect the broadening of the phonons to take the form of a damped harmonic oscillator function [24][25][26] 22 …”
Section: Phonon Shifts and Broadeningmentioning
confidence: 99%
“…Measurements of the phonon dispersions of bodycentered-cubic ͑bcc͒ transition metals [21][22][23][24][25][26] have shown that the quasiharmonic model cannot always be reconciled with the experimentally determined entropy of a solid. For chromium, considering only thermal expansion against the bulk modulus severely underestimates the entropy given by the softening of the phonon DOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation